Counter measures study on train swaying on the bridge induced by sudden change of wind force with wind barrier. (August 2022) - Tian, Zhang; Qianwen, Xu; Xinjia, Cui; Pengfei, Li; Yunfeng, Zou
In order to guarantee the running safety of the train on the bridge in the wind field the wind-proofing barrier is generally installed on the bridge, however, in the transition section where a train enters or exits the wind-proofing barrier the wind load on the car-body will suddenly change because of a sudden change of wind field. This will cause the train swaying, reduce the driving comfort, and even endanger the driving safety in severe cases. Therefore, it is necessary to optimize the wind barrier design in the transition section. Firstly the dynamic interaction model of vehicle-bridge-wind barrier coupling system under wind load is established, and the influence of sudden change of wind forces acting on the train on the driving safety is analyzed, then some concrete measures are proposed with respect to improving the driving comfort and safety and the effect of the optimizing measures is evaluated. Taking 12-span simply supported box girder bridges installing single-side 3.5 m wind barrier as an example, and optimizing the design of wind barriers in the transition section, the dynamic response and the driving safety indices of the train are obtained according to the above calculation model. The results before and after the optimization design of the wind barrier in the transition section are compared. It can be found that the sudden change of wind forces on the train induced by wind barrier has a significant effect on the lateral acceleration of the train, especially when the train is moving in and out of the wind barrier. The driving safety indices with gradual wind barriers are smaller than those without optimization design in the transition section of wind barrier.